METODOLOGIAS APLICADAS AO ENSINO-APRENDIZAGEM DE LÍNGUA INGLESA PARA FINS ESPECÍFICOS EM UNIVERSIDADES PARANAENSES - Elaine de Castro (2022)
Considering the growing demand for the English Language (EL) in economic, political, and social relations on a global scale, as well as its implications in the professional sphere of several knowledge areas, the expansion of English teaching and learning is linked to these changes, reinforcing a purpose-driven teaching-learning approach. Based on the concept of English for Specific Purposes (ESP), this study presents an overview of Foreign Language (FL) teaching and learning internationally and nationally, until the consolidation of ESP and its space in academic research and curriculum in Higher Education. Thus, the main objective is the analysis of the offer and execution of ESP disciplines in public universities in Paraná, focusing on their methodological, didactic, and organizational aspects, as well as the teaching practice of professionals inserted in them. To this end, the methodological approach involved the Document Analysis of curricular matrices, pedagogical projects, course programs and teaching plans available on the websites of the campuses of state universities, aiming to map disciplines and higher courses which offer ESP in their grid. From the delimitation of Tourism, Executive Secretariat and International Relations courses, semi-structured interviews were carried out with professors from four institutions, which accepted to participate in the study, with the aim of showing how the ESP approach is conceived and put into practice in their contexts. The transcripts were analyzed under the approach of Content Analysis and the Appraisal Theory, through linguistic-discursive elements and the interpersonal meaning expressed by the participants. Based on these data, a critical and comparative analysis of ESP curricula and programs of the institutions was carried out. From that, it was possible to verify that the teaching practices present similarities in organizational aspects regarding workload, class division, and ESP discipline planning of the programs. These factors are directly impacted by the learners’ demands and the needs of the target situation, in addition to elements permeating this process, such as the students’ profiles and the resources offered by the institutions themselves. In this sense, in line with the theoretical-methodological parameters of ESP, some principles of action are suggested, taking into account the model of the courses and the reported teaching-learning needs. Thus, this study intends to offer paths and proposals for the strengthening of the analyzed programs and, on the other hand, propose new ESP initiatives for these and other courses that apply this approach. Keywords: Language teaching and learning; English language; English for Specific Purposes; Higher education.